2008
DOI: 10.4049/jimmunol.180.5.3520
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Responses to TREM-1 Activation: Overlap, Divergence, and Positive and Negative Cross-Talk with Bacterial Lipopolysaccharide

Abstract: TREM-1 (triggering receptor expressed on myeloid cells-1) is an orphan immunoreceptor expressed on monocytes, macrophages, and neutrophils. TREM-1 associates with and signals via the adapter protein DAP12/TYROBP, which contains an ITAM. TREM-1 activation by receptor cross-linking has been shown to be proinflammatory and to amplify some cellular responses to TLR ligands such as bacterial LPS. To investigate the cellular consequences of TREM-1 activation, we have characterized global gene expression changes in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
158
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(171 citation statements)
references
References 95 publications
5
158
0
8
Order By: Relevance
“…Nevertheless, in another study it was demonstrated that E. coli LPS does not affect TREM-1 transcription in peripheral blood monocytes, but causes an increase in cell surface TREM-1 expression, denoting an effect on post-transcriptional modulation (Wong-Baeza et al, 2006). These seemingly conflicting results could be partly explained by recent evidence using microarray technology, suggesting that there is both positive and negative cross-talk between LPS and TREM-1 signalling in human monocytes (Dower et al, 2008). Moreover, Salmonella abortus LPS was shown to cause a transient increase of cell-surface TREM-1 at 6 h, succeeded by an increase of sTREM-1 at 24 h (Gomez-Pina et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, in another study it was demonstrated that E. coli LPS does not affect TREM-1 transcription in peripheral blood monocytes, but causes an increase in cell surface TREM-1 expression, denoting an effect on post-transcriptional modulation (Wong-Baeza et al, 2006). These seemingly conflicting results could be partly explained by recent evidence using microarray technology, suggesting that there is both positive and negative cross-talk between LPS and TREM-1 signalling in human monocytes (Dower et al, 2008). Moreover, Salmonella abortus LPS was shown to cause a transient increase of cell-surface TREM-1 at 6 h, succeeded by an increase of sTREM-1 at 24 h (Gomez-Pina et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Since the TREM-1 / DAP12 signalling pathway can amplify inflammation, and since it overlaps, in both positive and negative cross-talks with pathways known to be activated by P. gingivalis (Dower et al, 2008;Pathirana et al, 2010), there is merit to investigate whether and how this species may regulate the expression of TREM-1 / DAP12.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most compelling was the apparent activation of the TREM-1 (and related LPS) signaling pathway in subjects with suboptimal asthma control. Enrichment was noted for six gene sets that were differentially expressed in circulating murine monocytes in response to stimulation with TREM-1, LPS, or both (30). TREM-1 is a critical amplifier of inflammatory responses induced by tolllike receptor 4 (27) and other patternrecognition receptors (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Expressed on monocytes, macrophages, and neutrophils, TREM-1 is an orphan immunoreceptor that amplifies inflammation induced by patternrecognition receptors (28) and interacts with the toll-like receptor 4 to promote LPS-mediated granulocytic inflammation (27,29). These two molecules were represented by six replicated gene sets enriched during suboptimal control that came from the C7 subcollection GSE9988 ("Innate immune responses to TREM-1 activation") (see Table E4), which consists of profiles derived from a study of monocyte gene expression following treatment with either a TREM-1 activating antibody, LPS, or both (30).…”
Section: Novel Biologic Insights Into Asthma Controlmentioning
confidence: 99%
“…20,21 The activation of these pathways ultimately leads to a mobilization of intracellular calcium, a rearrangement of the actin cytoskeleton and activation of transcriptional factors such as NFκB. This finally results in production of metalloproteases, 22 pro-inflammatory cytokines and chemokines, [11][12][13]16,23 including MCP-1, MIP1-α, IL-1β, IL-6, IL-8, TNFα, along with rapid neutrophil degranulation and oxidative burst, 12,21 with a parallel negative regulation of anti-inflammatory IL-10. 16 Of note, although crystallographic analyses 24,25 can predict TREM-1 recognition by using antibody-equivalent complementary determining regions (CDR) loops (such as TCRs, CD8 and CTLA-4), its natural ligand has yet to be determined.…”
Section: Trem-1 Structure and Functionmentioning
confidence: 99%